A guide to speech production and perception - Tatham, Mark (Edinburgh University Press, 2011)
What roles do the speaker and the listener play in communication processes? Providing an overall system view, this innovative textbook explains how those working in the area think about speech. Emphasising contextual and environmental perspectives, Tatham and Morton lead you through classical and modern phonetics alongside discussion of cognitive and biological aspects of speech. In explaining speech production-for-perception and the relationship between phonology and phonetics, this book shows the possible applications (such as language teaching, clinical practice and speech technology) and how these are relevant to other disciplines, including sociolinguistics, cognitive neuroscience, psychology and speech acoustics.